Clinical outcome of percutaneous lumbar foraminoplasty using a safety-improved device in patients with lumbar foraminal spinal stenosis - Yoo, Yongjae (Medicine (Baltimore), 2019)
Lumbar foraminal spinal stenosis (LFSS) is defined as the narrowing of the nerve root exit associated with a herniated intervertebral disc, osteoarthritic changes in the facet joints, or a hypertrophied ligamentum flavum, which can provoke neurogenic claudication. To achieve effective and safe decompression of the lumbar spinal foramen, a specially designed instrument (Claudicare, SEAWON Meditech, Bucheon-si, Gyeonggi-do, Republic of Korea) for percutaneous lumbar foraminoplasty (PLF) was invented. The purpose of this study was to evaluate the clinical efficacy and safety of the newly devised instrument in patients with LFSS. PLF was performed for LFSS by a single pain physician. For each patient, an 11-point numerical rating scale (NRS) pain score—the Oswestry Disability Index (ODI)—and the duration of walking without radicular pain were evaluated at the 3-month follow-up. The successful responder percentage was defined as ≥50% reduction from the baseline NRS score with improvement in ODI and duration of walking. Among 24 patients who underwent PLF, 15 patients showed successful responses. The NRS pain score and duration of walking without radicular pain were improved significantly from baseline at the 3-month follow-up (P < .01). The ODI was also decreased, but the difference was not statistically significant (P = .09). The NRS pain score and walking duration without pain at 3 months were statistically significantly different between the groups (P < .001 and P = .01, respectively), whereas there was no statistically significant difference in improvement in ODI between the groups (P = .23). No serious adverse events occurred in the study. In conclusion, PLF using the Claudicare device may be an optimal and safe option for managing intractable LFSS on an outpatient basis.